A Middle Pleistocene abrading tool from Tabun Cave, Israel: A search for the roots of abrading technology in human evolution. Issue 150 (January 2021) - Shimelmitz, Ron; Groman-Yaroslavski, Iris; Weinstein-Evron, Mina; Rosenberg, Danny
Abstract: During the reanalysis of the finds from Jelinek's and Ronen's excavations at Tabun Cave, Israel, we encountered a cobble bearing traces of mechanical alterations similar to those recorded on grinding tools. However, the artifact derives from the early layers of the Acheulo-Yabrudian complex of the late Lower Paleolithic (ca. 350 ka), a time with no evidence for grinding or abrasion. Accordingly, we sought to determine whether the traces on the artifact can be attributed to purposeful human action. We conducted a detailed use-wear analysis of the cobble and implemented an experimental program, gaining positive results for the hypothesis of purposeful human practice. We argue that the significance and novelty of early abrading technology is that it marks a new mode of raw material manipulation—one that is categorically different from other modes of tool use observed among earlier hominins or other primates and animals. Throughout the Early Pleistocene, use of stone tools was associated with vertical motions (battering, pounding, striking) or with the application of a thin or narrow working edge, leveled at cutting or scraping. Conversely, abrading consists in applying a wide working surface in a continuous sequence of horizontal motions, geared to modify or reduce the surfaces of a targeted material. The emergence of this technology joins additional behavioral changes recently identified and attributed to the Middle Pleistocene, illustrating the growing and diversifying capabilities of early hominins to harness technology to shape their environment.